Avaliação da qualidade da água e sedimento de microbacias utilizadas para abastecimento público da região metropolitana de Goiânia - Batista, Maria Alciony Rosa da Silva (2015)
Water resources used for human consumption have been changing due to population growth that occurs often in a disorganized way, and the growing expansion of agriculture and industry, thus leading to degradation of water sources. Thus, given the impacts on water resources, it was established that water intended for human consumption must meet quality standards prepared in Resolution CONAMA No. 357/2005. This resolution regulates the quality standards which water intended for human consumption must have so that after treatment, can be used by the population. However, although the water for human consumption should be protected to prevent any contamination, it does not mean that this will be according to law. This is due to the fact that water resources in general, end up being the final destination of various types of pollutants. Thus, it is necessary to carry out analysis of sediments to complement the analysis of water quality that is intended for human consumption due to the fact that he act as a potential source of contaminants. Given the above, the objective of this study was to evaluate the water quality and sediment of four supply sources located in the metropolitan area of Goiânia/GO – Recanto Dourado, Ribeirão das Lajes, Córrego Vereda e Córrego Bom Sucesso. The study was divided into two chapters. The first chapter evaluated the quality of water sources from the results obtained from carrying out the temperature analysis, pH, electrical conductivity, DO, BOD, total nitrogen, total phosphorus, total dissolved solids, total coliforms and Escherichia coli in the water. In the sediment, pH analyzes,% moisture,% organic matter and particle size were performed. The four supply sources were evaluated as belonging to the fresh water Class II according to CONAMA Resolution 357/2005. The results of physicochemical parameters have OD values and total phosphorus at odds with the established by legislation to fresh water Class II. In the second chapter, the quality of water and sediment of these four rivers was evaluated through the analysis of metals Cd, Cr, Cu, Ni, Zn and Pb. Only copper (Cu) concentrations were found, in water, in disagreement with the maximum values established by law. In the sediment there were no disagreements metal concentrations because all were below the established by the legislation. As the results of these parameters, except for the OD and total phosphorus, it can be concluded that these water supply sources, even displaying some kind of impact, in general, have good water quality, and may continue to be used for public supply. However, in all the rivers were found problems that can compromise their future use as water supply source such as loss of forest cover and silting. This, is needed continuous monitoring and the establishment of recovery actions of these water sources in order to ensure not only water quality, but its future permanence as source of water supply.